Institutional investors and house prices - Emil Bandoni; Giorgia De Nora; Margherita Giuzio; Ellen Ryan; Manuela Storz (European Central Bank (ECB), 2025)
Institutional investors, such as investment funds, are playing an increasingly important role in residential real estate markets. This raises the possibility that their actions might drive aggregate market outcomes and may change how and which macrofinancial shocks transmit to house prices. In a Bayesian vector autoregression setting, we show that a demand shock from institutional investors has a positive and persistent effect on aggregate euro area house price growth and mortgage lending volumes. Institutional investors also increase their purchase activity following a loosening of monetary policy. Exploiting regional heterogeneity in eight euro area countries, we show in a panel regression setting that institutional investors weaken the link between house price growth and local economic fundamentals, but strengthen the sensitivity to monetary policy and financial market developments.
Keywords: R31; E52; G23; 330; Real estate; financial stability; non-bank financial intermediation; investment funds; monetary policy